The integration of religious and science curriculum in the implementation of the jsit curriculum at sdit salsabila yogyakarta - Triana Hermawati; Nur Fadilah Tanjung; Tsaniyatush Shoolihah Fauzan; Imam Suyuti; Akhsanul Fuadi (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
Achieving success in both worldly and hereafter matters requires a systematic process, through the practice of worship and education that is purposefully designed with the support of a structured curriculum. Currently, the National Education System is considered not yet fully capable of meeting the demands of the times and the expectations of society. This situation has led to the emergence of Integrated Islamic Schools, including SDIT Salsabila Yogyakarta, which operates under the Integrated Islamic School Network (JSIT), offering a concept of integration between religious education and science. This study aims to analyze the implementation of the JSIT curriculum as a model of integrating religion and science at SDIT Salsabila Yogyakarta. The research employed a qualitative method with a descriptive approach. The results show that the curriculum integration at SDIT Salsabila is carried out through the combination of three main curricula: the JSIT Curriculum, the National Curriculum (from the Ministry of Education and the Ministry of Religious Affairs), and the Qur'an Curriculum (tahfidz program). The integration model developed focuses more on strengthening Islamic values as the foundation of all academic activities, while the science component is applied more practically in everyday life. Through this approach, SDIT Salsabila Yogyakarta strives to nurture students who are not only knowledgeable but also possess strong faith and good character (Research, 2025).